Interactions of Ascorbic Acid with Satraplatin and its trans Analog JM576: DFT Computational Study - Šebesta, Filip; Burda, Jaroslav V. (European journal of inorganic chemistry, 2018)
Knowledge of the mechanisms for the reduction of PtIV anticancer prodrugs is of great importance, since the reduction process is considered as a necessary step for their activation. Therefore, in this study, we investigate the reduction of satraplatin {JM216, cis,trans,cis‐[PtCl2(OAc)2(cha)(NH3)], cha = cyclohexylamine} by ascorbic acid (AA) where proton‐assisted electron‐transfer and outer‐sphere electron‐transfer mechanisms are employed. Also, the presence of an additional base, which should increase the concentration of the deprotonated AA2– form, is discussed. Structures are optimized at the B3LYP‐GD3BJ/6‐31+G(d)/MWB60/C‐PCM/Klamt level and single‐point calculations are performed in the larger 6‐311++G(2df,2pd)/MWB60 basis set, together with the better implicit solvation model – IEF‐PCM/scaled‐UAKS. All three protonation states of ascorbic acid are taken into consideration. An effective rate constant of 2.6 × 10–3 m–1 s–1 is obtained from the kinetic formalism for side reactions, as described recently. For the reduction of satraplatin by fully deprotonated ascorbic acid, changes of the electron‐density distribution along the reaction coordinate are further investigated using NPA, QTAIM, and reaction electronic‐flux analysis. Both electron‐transfer mechanisms are also explored for the satraplatin trans analog JM576 {trans,trans,trans‐[PtCl2(OAc)2(cha)(NH3)]}. The resulting effective rate constant of 5.1 × 10–2 m–1 s–1 is compared with available experimental data. The reduction of satraplatin with ascorbic acid is investigated. Three protonation forms of the ascorbic acid are considered. The formalism of side reactions is applied in the kinetic model, since a low activation barrier is found for AA2–, whose concentration is negligible at neutral pH. Thus, the effective rate constant is in fair agreement with experimental data.